A Baxter family Christmas - Kingsbury, Karen (Waterville, Maine : Wheeler Publishing, 2016)
"Two years have passed since the terrible car accident that took the life of John Baxter's daughter, Erin, her husband and three of their four daughters. John has invited a stranger for Christmas Eve dinner - Kendra Bryant, the transplant recipient who now has Erin's heart. Ashley and her brother Luke don't think it is right; they want to protect their ten-year-old niece, Amy - the only surviving member of the accident. Kendra Bryant has been struggling these past few years to find purpose in the tragedy that gave her a second chance. She believes the invitation to see the Baxters and witness their unwavering faith in God can instil peace and happiness back into her life" -- page [4] cover.
"Wheeler Publishing Large Print Hardcover" -- Title page verso.
Keywords: Families -- Fiction; Heart -- Transplantation -- Patients -- Fiction; Christmas stories